1991
DOI: 10.1161/01.cir.84.2.665
|View full text |Cite
|
Sign up to set email alerts
|

Electrode system influence on biphasic waveform defibrillation efficacy in humans.

Abstract: Biphasic pulsing was useful with nonthoracotomy lead systems as well as with epicardial lead systems. However, the degree of biphasic waveform defibrillation superiority appeared to be electrode system dependent. Furthermore, for a few individuals, biphasic waveform defibrillation proved less efficient than monophasic waveform defibrillation, regardless of the lead system used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Prior research has demonstrated, for example, that the increased defibrillation efficacy of biphasic versus monophasic waveforms is influenced by electrode configuration. 16 Further, the optimal phase 1 duration and capacitance may vary with electrode configu-ration and pathway resistance. 10,17 Perhaps most importantly, because these conflicting studies used a much smaller sample size (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) patients) than the current study, they would have had a low probability of detecting 10%-15% differences in defibrillation efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated, for example, that the increased defibrillation efficacy of biphasic versus monophasic waveforms is influenced by electrode configuration. 16 Further, the optimal phase 1 duration and capacitance may vary with electrode configu-ration and pathway resistance. 10,17 Perhaps most importantly, because these conflicting studies used a much smaller sample size (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) patients) than the current study, they would have had a low probability of detecting 10%-15% differences in defibrillation efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…First, the unipolar pulsing method uses a biphasic waveform, and this particular biphasic waveform has been shown to improve defibrillation efficacy in previous studies.15 17,20 Second, the current vector is directed from right to left and inferior to superior. Depending on the RV defibrillation coil location on the diaphragmatic surface of the right ventricle, the current also may be directed through the heart in a posterior to anterior direction.…”
Section: Discussionmentioning
confidence: 99%
“…These trials focus on searching for optimal forms of defibrillation impulse, as well as on the development of properties and placement of defibrillation leads. 1,3,11,17,19,25,30 Optimization of the lead system and positioning aims to lower the voltage defibrillation threshold (V th ), or minimum shock strength needed to eliminate fibrillatory wavefronts, so as to increase success rates for defibrillation shocks, decrease myocardial tissue damage, and increase the lifespan of the ICDs. 12,13,22,28,31 Because defibrillation mechanisms are still largely not understood and experimental studies are difficult to conduct due to the need to test numerous electrode positions, computer models have been applied for the optimization analysis.…”
Section: Introductionmentioning
confidence: 99%